Topics in several complex variables - USA-Uzbekistan Conference on Analysis and Mathematical Physics (California, CA 20-23 May 2014); Ibragimov, Zair; Levenberg, Norman; Pinchuk, Sergey; Sadullaev, Azimbay (Providence : American Mathematical Society, 2016)
This volume contains the proceedings of the Special Session on Several Complex Variables, which was held during the first USA-Uzbekistan Conference on Analysis and Mathematical Physics from May 20-23, 2014, at California State University, Fullerton. This volume covers a wide variety of topics in pluripotential theory, symplectic geometry and almost complex structures, integral formulas, holomorphic extension, and complex dynamics. In particular, the reader will find articles on Lagrangian submanifolds and rational convexity, multidimensional residues, S-parabolic Stein manifolds, Segre varieties, and the theory of quasianalytic functions.
Includes bibliographical references and index.
Keywords: Functions of several complex variables -- Congresses